Intervention in overweight and obese schoolchildren, Tunja II semester 2013 (Impetus, 2021)
In the 20th century, many human behaviors changed due to the advance of industrialization and increased income. These changes had immediate consequences on people's lifestyles, leading to the emergence of new concerns, including those related to the area of ​​health. Therefore, it is not surprising that obesity and being overweight are today considered a public health problem. Among the most obvious lifestyle changes associated with the obesity phenomenon during the 20th century are: industrial processing, increased car use, expansion of fast food culture, and sedentary lifestyle. All of this has been called the post-industrial nutritional revolution.